Model Pengembangan Kurikulum Mata Kuliah Pengembangan Kepribadian dalam Merespon Era Informasi Digital - Karim, Mohammad (J-PAI: Jurnal Pendidikan Agama Islam, 2020)
Abstract. University graduates are expected to be individuals who deserve to be emulated. Their way of thinking, behaving and spiritual mentality become an example in society. But that is not always the case. There is a phenomenon that highly educated people are easily influenced by false information. Thus, there are some questions the college curriculum in preparing graduates with good character. This research aims to find the formulation of the ideal model for curriculum development in Personality Development Courses in tertiary institutions. This research paradigm is interpretive. The research approach is qualitative. The type of research is Multi Site-Study. Collecting data in methods participation, observation, documentation and interviews. Data analysis in the form of categorization, meaning, comparison and generalization. The data validity test was triangulation. The data presentation is descriptive. This study reports that the curriculum development model for Personality Development Subjects can be done by first identifying graduate performance and user responses. Then compile graduate profiles, teaching materials, process standards and evaluation.